Protótipo de aplicação web para identificação de técnicas de levantamento de requisitos utilizando lógica fuzzy - Paula, Erick Tauã Amaral de (2023)
One of the most crucial phases in web development is requirement elicitation. Each application requires a suitable requirement elicitation process tailored to its context, raising the question of how to decide on the best technique for the project. To address this, a web application has been developed that utilizes fuzzy logic to assist in choosing the requirement elicitation technique based on information about the project and the development team. The validity of the application was obtained through questionnaires with professionals in the software development field.